REHABILITATION OF RESPIRATORY FUNCTION IN PERSON WITH BACTERIAL PNEUMONIA SECONDARY TO INFLUENZA A: CASE STUDY - Pedro Raposo; Catarina Simão; Helena Pestana; Ana Cristina Mesquita; Luís Sousa (Associação Portuguesa dos Enfermeiros de Reabilitação, 2019)
Background: The autumn and winter months are associated with an increase in the seasonal epidemic flu responsible for 3 to 5 million cases of serious illness. Secondary bacterial infection is the most frequent complication, with high hospitalization rates. The rehabilitation nurse is recognized for being specialist in therapeutic interventions to provide the recovery of the person with respiratory pathology. Objective: To identify health outcomes from rehabilitation nursing care associated with the optimization of the respiratory function in a person diagnosed with streptococcus pneumonia community-acquired pneumonia secondary to Influenza A infection. Method: Qualitative case study research type. The study highlights the nursing care using the Padrão Documental dos Cuidados da Especialidade de Enfermagem de Reabilitação in an elderly person with altered respiratory function is presented, necessitating oxygen therapy and with its ability to expectorate compromised. The ethical principles in research have been fulfilled. Results: The implementation of the intervention plan constituted by four days revealed a reduction in the sensation of dyspnea; reduction of oxygen therapy; reduction of secretions; improvement in pulmonary auscultation of the vesicular murmur. Conclusions: It is verified that the implementation of an individualized rehabilitation nursing care plan can contribute significantly to promote the recovery of the person with restrictive respiratory pathology.